O09.4 Assessment of clinic and community recruited young african american women for prep eligibility in atlanta, georgia. (8th July 2017) - Sales, Jessica; Sheth, Anandi; Steiner, Riley; Brown, Jennifer; Swarzendruber, Andrea; Cwiak, Carrie; Haddad, Lisa; Patel, Anar
Abstract : Introduction: HIV disproportionately impacts African Americans (AAs) in the US. Atlanta has been identified as an HIV 'hot spot' for AA women and ranks 8th in the US with new infections. Yet little is known about PrEP eligibility or interest among young AA women in Atlanta. Methods: 1261 sexually active young AA women (14–24 years) provided baseline data on self-reported sexual behaviour and laboratory-confirmed STI testing (Chlamydia (CT) and gonorrhoea (GC)) prior to participating in an HIV prevention trial in Atlanta. A convenience sample of women were recruited from 2 settings: community venues (n=560, ages 18–24, 2012–2014) and sexual health clinics (n=701, ages 14–20, 2005–2008) from sexual health clinics. An HIV risk index capturing key HIV risk factors for women was calculated from the self-report data. For the clinic sample the index included recent (past 90 days) condomless vaginal sex, condomless anal sex, sex with partner who has had male partners, sex while high (self), sex while high (partner), and intimate partner violence (IPV) (range: 0–6). For the community sample, the index included condomless sex at last sex, exchanged sex for goods and experienced IPV in past 90 days (range: 0–3). A single item assessed PrEP interest in the community sample only. Results: Bacterial STI positivity, a primary indicator for PrEP eligibility, was 20.5% (17.1% CT, 6.3% GC) and 20.9% (18.8% CT, 5.2% GC) for the clinic and community samples, respectively. Of the 144 STI positive women from the clinic sample, HIV risk index scores ranged from 0–4, with 21.5% reporting no other HIV risk indicators, 31% had one, 27.8% two, 16.7% three and 2.8% had 4 additional indicators. Of the 117 STI positive women from the community sample, HIV risk index scores ranged from 0–3, with 51.3% reporting no other indicators, 36.8% one, 10.3% two and 1.7% had all 3 additional indicators. Among STI positive women, the most common HIV risk indicator was condomless vaginal sex, but 23.8% and 13.2% (only reported by those >18 years) of the community and clinic samples, respectively, reported recent IPV. 57.8% of the community sample reported they would be likely or very likely to use PrEP if available. Conclusion: Our findings indicate that young AA women in Atlanta, whether sampled from community venues or sexual health clinics, are at substantial risk for HIV and meet several PrEP eligibility criteria. Scaling up PrEP among women in Atlanta could have significant implications for HIV in this high burden region.